RNA-binding protein nucleolin in disease - Abdelmohsen, Kotb; Gorospe, Myriam (RNA biology, 2012)
Nucleolin is a multifunctional protein localized primarily in the nucleolus, but also found in the nucleoplasm, cytoplasm and cell membrane. It is involved in several aspects of DNA metabolism, and participates extensively in RNA regulatory mechanisms, including transcription, ribosome assembly, mRNA stability and translation, and microRNA processing. Nucleolin's implication in disease is linked to its ability to associate with target RNAs via its four RNA-binding domains and its arginine/glycin-rich domain. By modulating the post-transcriptional fate of target mRNAs, which typically bear AU-rich and/or G-rich elements, nucleolin has been linked to cellular events that influence disease, notably cell proliferation and protection against apoptotic death. Through its diverse RNA functions, nucleolin is increasingly implicated in pathological processes, particularly cancer and viral infection. Here, we review the RNA-binding activities of nucleolin, its influence on gene expression patterns, and its impact upon diseases. We also discuss the rising interest in targeting nucleolin therapeutically.